Sex Bias and Maternal Contribution to Gene Expression Divergence in Drosophila Blastoderm Embryos. - Paris, M.; Villalta, J.E.; Eisen, M.B.; Lott, S.E. (PLoS Genetics, 2015)
Early embryogenesis is a unique developmental stage where genetic control of development is handed off from mother to zygote. Yet the contribution of this transition to the evolution of gene expression is poorly understood. Here we study two aspects of gene expression specific to early embryogenesis in Drosophila: sex-biased gene expression prior to the onset of canonical X chromosomal dosage compensation, and the contribution of maternally supplied mRNAs. We sequenced mRNAs from individual unfertilized eggs and precisely staged and sexed blastoderm embryos, and compared levels between D. melanogaster, D. yakuba, D. pseudoobscura and D. virilis. First, we find that mRNA content is highly conserved for a given stage and that studies relying on pooled embryos likely systematically overstate the degree of gene expression divergence. Unlike studies done on larvae and adults where most species show a larger proportion of genes with male-biased expression, we find that transcripts in Drosophila embryos are largely female-biased in all species, likely due to incomplete dosage compensation prior to the activation of the canonical dosage compensation mechanism. The divergence of sex-biased gene expression across species is observed to be often due to lineage-specific decrease of expression; the most drastic example of which is the overall reduction of male expression from the neo-X chromosome in D. pseudoobscura, leading to a pervasive female-bias on this chromosome. We see no evidence for a faster evolution of expression on the X chromosome in embryos (no "faster-X" effect), unlike in adults, and contrary to a previous study on pooled non-sexed embryos. Finally, we find that most genes are conserved in regard to their maternal or zygotic origin of transcription, and present evidence that differences in maternal contribution to the blastoderm transcript pool may be due to species-specific divergence of transcript degradation rates.